Development of a knowledge assessment tool to measure the knowledge level of farmers about rapeseed-mustard cultivation (Journal of Oilseed Brassica, 2025)
Rapeseed-mustard is a crucial oilseed crop widely cultivated by farmers; however, a noticeable gap exists between scientific recommendations and actual farming practices, leading to suboptimal yields. This study aimed to develop a standardized knowledge test to assess farmers’ understanding of rapeseed-mustard cultivation practices, with the ultimate goal of identifying knowledge gaps that hinder optimal crop management. The test construction involved a comprehensive process, including a literature review, expert consultations, and field surveys to determine key practices such as soil preparation, seed treatment, irrigation schedules, pest and disease management, and post-harvest handling. A preliminary test was administered to 60 farmers to ensure clarity, reliability, and validity. Item analysis was conducted using difficulty and discrimination indices, resulting in a refined set of 28 items from an initial 36 statements. Findings revealed that most farmers (55.83%) possessed moderate knowledge, while 26.67% had low knowledge and 17.55% had high knowledge of recommended practices. This knowledge test is a valuable tool for agricultural extension professionals to assess farmers’ knowledge and provides insight into specific areas where training and support are needed. By targeting these gaps, extension services can deliver tailored education programs that foster sustainable practices and improve productivity in rapeseed-mustard farming.